J.L.Runeberg’s idyllic reality. Notes on his early works - Mrozewicz, Bolesław (Folia Scandinavica Posnaniensia, 2007)
In the paper the early works of J.L.Runeberg, the Finnish national romantic, are analysed. The paper presents Runebeig’s idealistic and romantic views on the Finns and the Finnish reality in the first half of the 19th century. Runeberg developed his opinions in the years 1823-26 which he spent among common people of Saarijärvi parish. In his early works Runeberg gave a , picture of an idealistic utopia in which all conflicts disappeared and everyone and eveiything lived in total harmony.